Chameleon Robot: An Innovative Approach to Teaching Colors - Lima, João P. R. de; Costa, Fabio A. S.; Teixeira, Eduarda R. da S.; Teixeira, Mariana R. da S.; Araújo, Niviton V.; Rossiter, Sarah T. de S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This project aims to design and build a chameleon robot capable of exploring various environments and changing its color according to the RGB color model to blend into its surroundings. With this innovative approach, we intend to introduce educational robotics into classrooms, offering students a unique experience in learning about colors and their compositions. This is our second project, improved based on the experiences and lessons from the first one. The interdisciplinary project will integrate concepts from design, physics, and arts, with the goal of stimulating student's interest and providing a more comprehensive and practical understanding of colors. By exploring the possibilities of robotics, we aim to make learning more engaging and captivating, encouraging an innovative approach to teaching.